2015
DOI: 10.1177/0533316415588253
|View full text |Cite
|
Sign up to set email alerts
|

A Soldier’s Matrix: A Group Analytic View of Societies in War

Abstract: In this article 1 I will discuss the question of violence in (large) groups and the relationship between the mass and the individual selves. This will be done through the concept of the 'soldier's matrix' 2 . I refer to a matrix dominating a whole society, which participates in organized aggression and suffers its emotional consequences. Everybody in the matrix becomes a soldier, and the identity or the 'Habitus' (Elias, 1989) of the society is influenced by soldiership. This applies not only to Iraq and Afgha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 9 publications
(14 reference statements)
1
21
0
1
Order By: Relevance
“…Israeli group analyst, Robi Friedman () suggested that societies experiencing existential threat may develop a “soldier matrix” which influences not only soldiers, but all members of a society affected by conflict. When a soldier's matrix appears, group members are influenced by schizoid‐paranoid processes, and “murderous violence is not only legitimised, it also arouses collective unconscious strong defences against feelings of guilt, shame or empathy for the enemy's suffering” (p. 243).…”
Section: Israeli Leadership Inhabits a “Soldier's Matrix”mentioning
confidence: 99%
See 1 more Smart Citation
“…Israeli group analyst, Robi Friedman () suggested that societies experiencing existential threat may develop a “soldier matrix” which influences not only soldiers, but all members of a society affected by conflict. When a soldier's matrix appears, group members are influenced by schizoid‐paranoid processes, and “murderous violence is not only legitimised, it also arouses collective unconscious strong defences against feelings of guilt, shame or empathy for the enemy's suffering” (p. 243).…”
Section: Israeli Leadership Inhabits a “Soldier's Matrix”mentioning
confidence: 99%
“…Although the soldier's matrix determines the thinking of every member of a society, it is not monolithic and does not preclude disagreement: Friedman () believed that an “anti‐soldier matrix” can also develop. In Israel this appears in human rights organisations (such as B’Tselem, Peace Now, Human Rights Watch, Rabbis for Human Rights, Breaking the Silence), the left‐wing press (Haaretz), as well as academics, judges, and literary figures.…”
Section: Israeli Leadership Inhabits a “Soldier's Matrix”mentioning
confidence: 99%
“…Як приклад можна згадати класичну роботу D. Grossman "On killing" (1995), у якій описано зміни, біологічні, психічні та психосоціальні, що відбуваються внаслідок участі людини в активних бойових діях, коли вона вбиває супротивника, ворога. Ще одним класичним прикладом може бути дослідження Robi Friedman (2015). Для називання змін у світогляді вояка психоаналітик пропонує термін "матриця солдата".…”
unclassified
“…When a group becomes massified, confidence is derived from belonging to a mass bigger than each person. Their salvation is so soothing that group members stop thinking for themselves, and give up their individuality (Hopper and Weinberg, 2011), in a 'selfless relational disorder', which is typical in societies where there is a strong 'soldiers' matrix' (Friedman, 2015).…”
mentioning
confidence: 99%